Climate change and organizational management: toward a new paradigm. Issue 3 (12th September 2020) - Baccarani, Claudio; Brunetti, Federico; Martin, Jacques
Abstract : Purpose: The purpose of this paper is to tackle the grand issue of climate change in a managerial perspective by proposing a new type of management. Design/methodology/approach: Climate change has now been debated for many years, and in spite of different viewpoints, analyses and opinions, is a phenomenon that is accepted by all. There are thousands of studies on the nature of climate change and its consequences on the planet Earth and its inhabitants. However, there are few studies investigating the consequences of climate change on the founding tenets and practices of management. This paper aims to contribute to this facet of the issue. In the first part, it examines the main facts about climate change, their impact on businesses and proposes an adapted model of management for agriculture, industry, services and supply chains. In the second part, it advocates a shift in paradigm from the "maximization of profit" to the "maximization of well-being" as the foundation of a new managerial philosophy that can both address climate change and sustainability. Findings: Companies and managers are in a much better position than politicians and consumers to find a solution to climate change problems for the very reason that they are not stupid in Cipolla's (2011) sense. Companies and managers do have the power to rewrite the rules of the game in order to get to a firm and management metamorphosis. Starting from a return to company ownership by and for the company itself (not just external shareholders), a switch in purpose from profit-seeking to people's well-being, fair remuneration of stakeholders, progress as a measure of success and long-term orientation are suggested as new tenets in management. Research limitations/implications: Although this paper has several limitations (it may be too wide in scope, utopian, its ideas may sound unachievable and even sometimes naïve in their arguments), its starting point is very clear: the authors, as management scholars, must do something to try and stop the crash of economies and businesses in an ecological disaster. And its logic is very clear and straightforward as well: if people want things to change, then they have to change the foundations of management thinking, both in theory and in practice. The authors do not claim their solution is the only one or the best: avenues for future research aimed at providing better solutions are wide open from this point of view, and the authors genuinely encourage colleagues to continue in this direction and contribute to this work. What matters most, however, is to stop looking for precise answers to "wrong, well-defined, narrow problems" and to start looking for "approximate answers to important problems" (Brown et al., 2005) as the authors tried to do here. Practical implications: Developing a new management operating model and foundations able to keep companies alive while not compromising mankind survival on planet Earth. Originality/value: This paper addresses the Tourish (2020) challenge for purposeful research in management by providing some fresh ideas about the way companies and management principles and practices should change to prevent irreversible environmental damages.